A SURVEY OF ETHNOMEDICINAL PLANTS USED BY LOCAL TRIBES OF AHERI AND BHAMRAGARH FOREST AREA OF GADCHIROLI DISTRICT IN MAHARASHTRA, INDIA - Dr. Sivaprasad Hari,; Ramesh R. Halami, (The Bioscan, 2025)
Aheri tahsil is located on the southern part of Gadchiroli district. Among the 12 tehsils, Aheri is the largest tehsil in the Gadchiroli district covering an area of 2282.70 km², while Desaiganj (Wadsa) is the smallest in the district, covering an area of 262.74 km². Chamorshi is the most populous whereas Bhamragad is the least populous tehsil in Gadchiroli district. A major portion of Aheri and Bhamragad areas are covered by forest and the ethnic group is Gond. The major local language is Gondi, however these people also know Marathi and Telugu as well. The current study covers both Aheri and Bhamragad tahsils. These tribals depend on forest resources for their daily needs including medicines. Usually they visit hakims (local doctor who prepare medicines from locally available plants only), for the treatment of any ailment.